Transitions in Medicine: Four-Year Complementary Process-Oriented Curriculum for Medical Student Guidance - Roy Strowd; Erika Borgerding; Sarah Kittner; Devin Haddad; Sara Fletcher; Marcia Wofford; Ann Lambros (Association of American Medical Colleges, 2014)
Abstract Introduction Numerous transitions exist in medical school-from undergraduate to medical education, from didactic to problem-based learning, from institutionally generated to national standardized examinations, from classroom study to clinical clerkship training, and from learning clinical medicine to determining a future career path. These transitions can have significant impact on academic performance, cynicism, dishonesty, substance abuse, depression, and suicidality. While faculty- and staff-led support programs are often offered to assist students, peer-led programs may provide even more support for coping with these transitions. Student mentoring has also been identified as an important factor in student satisfaction and career development during medical school. Methods Herein we describe a 4-year, noncompulsory course, Transitions in Medicine, that provides a mechanism for peer-led support and guidance through the many transitions in medical school. Recurring seminars focusing on process-oriented as opposed to content-oriented preparation are offered at key points within a student's medical school career. During each session, upper-class students provide targeted guidance and discussion about the important concepts, strategies, and preparation necessary at each transition. This resource includes an instructor's guide, PowerPoint and narrative descriptions of each seminar session, and a sample student survival guide designed to complement the 4-year course. Results This course has been effective and had significant impact on the culture of our institution. Several prior publications outlined in the resource have documented the effect of the course on student anxiety and academic performance. In addition, we offer further explanation of the tangible benefits that have been realized, including but not limited to benefits on student anxiety, early student planning, student preparedness, and student-to-student mentoring. Discussion The principle of "paying it forward" underlies student participation in this course. Students and faculty and have commented that as an apparent indirect benefit of the course, this important principle has been fostered and emphasized in its incorporation into the curriculum.